Drying of sliced tomato (Lycopersicon esculentum L.) by a novel halogen dryer: Effects of drying temperature on physical properties, drying kinetics, and energy consumption. (25th December 2020) - Al‐Hilphy, Asaad Rehman; Gavahian, Mohsen; Barba, Francisco J.; Lorenzo, José M.; Al‐Shalah, Zainab Musaddaq; Verma, Deepak Kumar
Abstract: This study aimed to explore the impact of halogen drying temperature (60, 70, and 80°C) on drying kinetics and some sensory and physical properties of tomato slices. Also, the suitability of previously proposed models for predicting the drying process of tomato slices was assessed and compared with that of a newly proposed model using root mean square error, reduced chi‐square, and determination of coefficient. According to the results, increasing the drying temperature from 60 to 80°C reduced the drying time from 150 to 106 min but increased energy consumption. Experimental drying curves indicated only one falling drying rate period for the drying temperatures of 60 and 70°C, while two consecutive falling rate periods were observed for drying temperatures of 80°C due to the case‐hardening phenomenon. The highest sensory score was obtained for samples dried at 60°C. Also, the effective moisture diffusion varied between 7.96 × 10 −9 and 1.07 × 10 −8 m 2 /s. The color parameters ( L *, a *, b *, a */ b *, and ∆ E ) of samples were significantly affected by drying temperature. The browning index and mass transfer coefficient increased significantly ( p < .05) with the increase of the drying temperature. The results introduced halogen drying as a promising processing technology for drying tomato slices. Practical applications: Drying, such as tomato slices drying, is one of the common process in the food industry. A novel drying technique, that is, halogen drying, was explored in the present study. This innovative process showed a good potential for upscaling, considering its ability in saving energy consumption, reducing drying time, and producing high‐quality products. Also, the effects of important process parameters, such as drying temperature, on the quality of the product were explained which can help with future commercial applications. Furthermore, the new mathematical models proposed in this study can be used by the industry to predict the quality parameters of the product and to achieve process automation. Abstract :